Fostering Classroom Communities through Circling With Teacher Candidates - Bouchard, Karen; Hollweck, Trista; Smith, J. David (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
Classroom circles have been recognized as a valuable pedagogical approach to develop students’ social-emotional learning and to establish a sense of community within a classroom. Until recently, there has been little consideration that teachers, themselves, may benefit from circling experiences. To garner a deeper understanding of circling for teachers, this study examined teacher candidates’ experiences with circling in a teacher education course. Focus groups with former teacher candidates procured three themes: circling creates safe and engaging spaces for learning, productive tensions create opportunities for connection, and, teachers create effective circles with authenticity. The results suggest that circling should be similarly used with educators, in addition to use with students, and could be embedded within current teacher-education programming.